Repetitive transcranial magnetic stimulation for treatment resistant depression: Re-establishing connections. Issue 11 (November 2016) - Anderson, Rodney J.; Hoy, Kate E.; Daskalakis, Zafiris J.; Fitzgerald, Paul B.
Highlights: Depression is associated with significant abnormalities in functional and structural connectivity. rTMS for treatment resistant depression modulates connectivity, normalising pre-treatment abnormalities. Connectivity imaging can be used to optimise rTMS targeting, explore and predict treatment response. Abstract: Repetitive transcranial magnetic stimulation (rTMS) is a relatively recent addition to the neurostimulation armamentarium for treating individuals suffering from treatment refractory depression and has demonstrated efficacy in clinical trials. One of the proposed mechanisms of action underlying the therapeutic effects of rTMS for depression involves the modulation of depression-associated dysfunctional activity in distributed brain networks involving frontal cortical and subcortical limbic regions, via changes to aberrant functional and structural connectivity. Although there is currently a paucity of published data, we review changes to functional and structural connectivity following rTMS for depression. Current evidence suggests an rTMS-induced normalisation of depression-associated dysfunction within and between large scale functional networks, including the default mode, central executive and salience networks, associated with an amelioration of depressive symptoms. Additionally, changes to measures of white matter microstructure, primarily in the dorsolateral prefrontal cortex, have also been reported following rTMS for depression, possibly reversing depression-associated abnormalities. We argue that measures of functional and structural connectivity can be used to optimise rTMS targeting within the dorsolateral prefrontal cortex and also to explore novel rTMS targets for depression. Finally, we discuss the utility of measures of brain connectivity as predictive biomarkers of rTMS treatment response in guiding therapeutic decisions.